A systematic review of osteoarthritis prevention and management with dietary phytochemicals from foods. (April 2019) - Guan, Vivienne X.; Mobasheri, Ali; Probst, Yasmine C.
Highlights: There is insufficient evidence on the relationship between dietary phytochemicals and osteoarthritis. Dietary polyphenols intake from foods may slow the progression of osteoarthritis. High-quality epidemiological studies and controlled trials are therefore required. Abstract: Osteoarthritis is the most prevalent chronic inflammatory joint disease affecting mobility in humans, as well as in companion and captive animals. Understanding the effect of dietary phytochemical intake from foods on osteoarthritis and its long-term outcomes may inform public health strategies for osteoarthritis prevention and management, reducing healthcare costs globally. The aim of this systematic review was to examine the effects of dietary phytochemical intake from foods on osteoarthritis in adult populations. A literature search was performed using Scopus, Web of Science, MEDLINE, PubMed and the Cochrane Library for human studies to identify randomised controlled trials (RCTs) and observational studies focused on osteoarthritis up to May 2018. From 5879 articles, five RCTs and four cross-sectional studies were identified. Dietary carotenoids were examined in the observational studies, while dietary intakes of polyphenols from foods were assessed in the RCTs. Dietary polyphenol intake from foods (e.g., freeze-dried strawberries and tart cherry juice) may slow the progression of osteoarthritis via decreased inflammation and reduced cartilage degradation. However, there were relatively few studies and a lack of uniformity in the biomarkers used and the measurements of pain, quality of life and physical activity relating to osteoarthritis. The heterogeneity among the studies suggests that there is insufficient evidence related to phytochemical intake from foods. High-quality epidemiological studies and controlled trials are therefore required. Nevertheless, exploring dietary phytochemical intake from foods may complement current dietary strategies for the management of osteoarthritis and help in the formulation of more economical and manageable strategies for osteoarthritis.